2007
DOI: 10.1111/j.1553-2712.2007.tb01846.x
|View full text |Cite
|
Sign up to set email alerts
|

Identifying Injection Drug Users at Risk of Nonfatal Overdose

Abstract: Drug users who have previously experienced a nonfatal overdose are at very high risk of experiencing future overdoses. Further longitudinal studies are needed to identify robust predictors of overdose risk over time in habitual drug users, but these data suggest that drug users who have overdosed warrant aggressive prevention efforts such as agonist maintenance treatment or provision of take-home naloxone.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
95
2
2

Year Published

2011
2011
2019
2019

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 93 publications
(105 citation statements)
references
References 45 publications
6
95
2
2
Order By: Relevance
“…The association between young age and overdose in multivariate Model 1 has been demonstrated in other studies. 10,11,14,32 Multiple studies have shown that young IDU are more likely to share syringes. [33][34][35] Over 63% of participants under 26 shared syringes or paraphernalia, compared to 42% of those 26 and over (pG 0.0001).…”
Section: G001mentioning
confidence: 99%
See 3 more Smart Citations
“…The association between young age and overdose in multivariate Model 1 has been demonstrated in other studies. 10,11,14,32 Multiple studies have shown that young IDU are more likely to share syringes. [33][34][35] Over 63% of participants under 26 shared syringes or paraphernalia, compared to 42% of those 26 and over (pG 0.0001).…”
Section: G001mentioning
confidence: 99%
“…[7][8][9] Polydrug use, binge drug use, alcohol use, and withdrawal symptoms have also been found to be associated with nonfatal overdose. 8,[10][11][12] Longer heroin-using career and greater heroin dependence have also been linked to nonfatal overdose. 12 Other risk factors include lifetime or recent incarceration experience, homelessness, syringe sharing, and homosexual or bisexual behavior.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Opioid dependence causes a significant amount of disease burden globally [1], and an Australian study estimated that 86% of deaths among patients receiving opioid substitution therapy were potentially preventable [2]. It is important to contextualize the discussion of unlicensed drug formulations so that we can weigh the risks versus the benefits in response to this timely question raised by Strang and colleagues, as well as keep in mind that it is the formulation and not the drug itself that is the focus of debate.We have a health state that causes significant premature mortality globally and a reversal agent that is not only efficacious, but also has an excellent safety profile [3] and is highly cost-effective [4]. Intranasal (i.n.)…”
mentioning
confidence: 99%